2021
DOI: 10.1007/s12117-021-09418-x
|View full text |Cite
|
Sign up to set email alerts
|

“Journey into hell […where] migrants froze to death”; a critical stylistic analysis of European newspapers’ first response to the 2019 Essex Lorry deaths

Abstract: In the early hours of October 23rd, 2019, 39 people were found dead in a refrigerated lorry in Grays, Essex, UK. This case attracted media interest across the world; in the 48-h period after the story broke, reporting on this discovery extended to newspapers not just in the UK, but also across Europe. This study uses elements of Critical Stylistics (Jeffries 2010) to analyse and compare first response articles published by European dailies in relation to the event at Grays, to address the nature of this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Most importantly, as is often the case after similar incidents (Mancini et al 2021), smugglers were held solely responsible for the wreck, having been accused of taking advantage of the desperate attempts of individuals trying to reach Europe. Moreover, some news reports suggested that the migrants and refugees on board themselves made the decision to relocate overseas, which led to their own hardship and fostered victimization, an aspect also noted by Gregoriou et al (2022). Anchored in the discourse and the agenda of official sources, the media under investigation was unable to draw attention to the range of issues surrounding migration at this time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most importantly, as is often the case after similar incidents (Mancini et al 2021), smugglers were held solely responsible for the wreck, having been accused of taking advantage of the desperate attempts of individuals trying to reach Europe. Moreover, some news reports suggested that the migrants and refugees on board themselves made the decision to relocate overseas, which led to their own hardship and fostered victimization, an aspect also noted by Gregoriou et al (2022). Anchored in the discourse and the agenda of official sources, the media under investigation was unable to draw attention to the range of issues surrounding migration at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, visual framing processes, such as pictures taken from above, presumably from a helicopter, yielding a birds-eye view perspective, depicting dead bodies floating on the surface of the blue sea, act to reinforce the dehumanizing narrative (Giubilaro 2018). Many media sources use object metaphors and describe smuggling as "business" or "commerce", using language that makes the trafficked seem as "currency", "shipments", or "cargo", "objects to manipulate" (Montagut and Moragas-Fernández 2020), while smugglers are portrayed as "machines" (Gregoriou et al 2022). Many media outlets quickly classify these individuals as migrants even though they are not really aware of their nationality.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations